Non-invasive, non-radiological quantificationof anteroposterior knee joint ligamentous laxity: A study in cadavers. Issue 11 (November 2013) - Russell, D. F.; Deakin, A. H.; Fogg, Q. A.; Picard, F.
Abstract : Objectives: We performed in vitro validation of a non-invasive skin-mounted system that could allow quantification of anteroposterior (AP) laxity in the outpatient setting. Methods: A total of 12 cadaveric lower limbs were tested with a commercial image-free navigation system using trackers secured by bone screws. We then tested a non-invasive fabric-strap system. The lower limb was secured at 10° intervals from 0° to 60° of knee flexion and 100 N of force was applied perpendicular to the tibia. Acceptable coefficient of repeatability (CR) and limits of agreement (LOA) of 3 mm were set based on diagnostic criteria for anterior cruciate ligament (ACL) insufficiency. Results: Reliability and precision within the individual invasive and non-invasive systems was acceptable throughout the range of flexion tested (intra-class correlation coefficient 0.88, CR 1.6 mm). Agreement between the two systems was acceptable measuring AP laxity between full extension and 40° knee flexion (LOA 2.9 mm). Beyond 40° of flexion, agreement between the systems was unacceptable (LOA > 3 mm). Conclusions: These results indicate that from full knee extension to 40° flexion, non-invasive navigation-based quantification of AP tibial translation is as accurate as the standard validated commercial system, particularly in the clinically and functionally important range of 20° to 30° knee flexion. This could be useful in diagnosis and post-operative evaluation of ACL pathology. Cite this article: Bone Joint Res 2013;2:233–7.